2010
DOI: 10.1021/pr1005229
|View full text |Cite
|
Sign up to set email alerts
|

A High-Throughput O-Glycopeptide Discovery Platform for Seromic Profiling

Abstract: Biomarker microarrays are becoming valuable tools for serological screening of disease-associated autoantibodies. Post-translational modifications (PTMs) such as glycosylation extend the range of protein function, and a variety of glycosylated proteins are known to be altered in disease progression. Here, we have developed a synthetic screening microarray platform for facile display of O-glycosylated peptides (O-PTMs). By introducing a capping step during chemical solid-phase glycopeptide synthesis, selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 50 publications
5
86
0
3
Order By: Relevance
“…It also differs from those of autoantibodies isolated from serum of tumor patients. [12] These divergent recognition selectivities probably can be traced back to different glycosylation positions in the MUC1 tandem repeat sequence 1:…”
Section: Dedicated To Professor Dieter Hoppe On the Occasion Of Hismentioning
confidence: 99%
See 1 more Smart Citation
“…It also differs from those of autoantibodies isolated from serum of tumor patients. [12] These divergent recognition selectivities probably can be traced back to different glycosylation positions in the MUC1 tandem repeat sequence 1:…”
Section: Dedicated To Professor Dieter Hoppe On the Occasion Of Hismentioning
confidence: 99%
“…The MUC1 tetanus toxoid vaccines [9] described above carried the T antigen or the sialyl-T N antigen side chains at threonine-6 of 1, whereas the SM3 antibody [10,11] as well as the autoantibodies in the sera of patients [12] showed intensive binding to MUC1 glycopeptides glycosylated in the GSTA region (Ser 17 , Thr 18 ). NMR spectroscopic analyses had shown that glycan side chains in the STAPPA peptide sequence of MUC1 influence the conformation of this peptide segment.…”
Section: Dedicated To Professor Dieter Hoppe On the Occasion Of Hismentioning
confidence: 99%
“…or in release of a part of the immobilised peptide derivative (proteases, phosphatases, histone deacetylases and lysine demethylases, etc.). Studies with kinases, phosphatases, proteases, (comprehensively reviewed in Table 1 in supplementary material), lysine methyl-transferases [117,118], arginine methyl-transferases [119], histone deacetylases [120][121][122][123], peptidyl-prolyl-cis/trans-isomerases [75,[124][125][126][127], glycosyltransferases [128][129][130], ADP-ribosyl-transferases [131,132], hydrolases [133], esterases [134] and ubiquitin-or SUMOligases [135][136][137] have been described using peptide arrays on cellulose membranes or peptide microarrays on glass slides. This review will summarise applications of peptide (micro)arrays for kinase, phosphatase and protease research in more detail.…”
Section: Assays and Detectionmentioning
confidence: 99%
“…To determine recognition sequence requirements for individual transferases, in vitro reactions involving purified enzymes and substrates are typically used 31À39 (a pH-based high-throughput assay for glycosyltransferase activity has been described, but it has not yet been used for the characterization of GalNAc-T isoforms 40 ). Recently, the in vitro use of glycosyltransferases has been extended to engineering applications such as the generation of glycopeptide libraries 41 and use in bioconjugate chemistry. 42 To find a suitable OGRS for hGalNAc-T2, we evaluated a small subset of the OGRS present in O-GlycBase v 6.00 for use as glycosylation targets on recombinant proteins.…”
Section: ' Introductionmentioning
confidence: 99%